1990
DOI: 10.1007/bf00010836
|View full text |Cite
|
Sign up to set email alerts
|

Soil restoration under pasture after topsoil removal: Some factors influencing C and N mineralization and measurements of microbial biomass

Abstract: Factors influencing rates of C and N mineralization of soil and plant materials, and the reliability of different procedures for estimating microbial biomass, were measured in a soil (Typic Dystrochrept) that had been restored under grazed pasture in a temperate environment for 10-11 years after 20 cm of the original topsoil had been removed by stripping.Rates of net N mineralization were appreciably lower, but C02-C production higher, in the stripped than in the unstripped soil. These activities were not infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…T h e microbial biomass during the rapid buildu p phases in plant succession is almost certainly related to both carbon and nitrogen limitation (Scheu, 1990;Zak et al, 1990), while later phases in the study of Scheu ( I 990) indicate the importance of phosphorus limitation also. Build-up of microbial biomass in the residual subsoil normally parallels the build-up of plants and soil organic matter and the microbial biomass has therefore frequently been proposed as an index of soil redevelopment (Ross et al, 1982;Durrall & Parkinson, 1987;Insam & Domsch, 1988;Srivastava, Jha & Singh, 1989;Ross et a / . Build-up of microbial biomass in the residual subsoil normally parallels the build-up of plants and soil organic matter and the microbial biomass has therefore frequently been proposed as an index of soil redevelopment (Ross et al, 1982;Durrall & Parkinson, 1987;Insam & Domsch, 1988;Srivastava, Jha & Singh, 1989;Ross et a / .…”
Section: A Wardlementioning
confidence: 99%
See 1 more Smart Citation
“…T h e microbial biomass during the rapid buildu p phases in plant succession is almost certainly related to both carbon and nitrogen limitation (Scheu, 1990;Zak et al, 1990), while later phases in the study of Scheu ( I 990) indicate the importance of phosphorus limitation also. Build-up of microbial biomass in the residual subsoil normally parallels the build-up of plants and soil organic matter and the microbial biomass has therefore frequently been proposed as an index of soil redevelopment (Ross et al, 1982;Durrall & Parkinson, 1987;Insam & Domsch, 1988;Srivastava, Jha & Singh, 1989;Ross et a / . Build-up of microbial biomass in the residual subsoil normally parallels the build-up of plants and soil organic matter and the microbial biomass has therefore frequently been proposed as an index of soil redevelopment (Ross et al, 1982;Durrall & Parkinson, 1987;Insam & Domsch, 1988;Srivastava, Jha & Singh, 1989;Ross et a / .…”
Section: A Wardlementioning
confidence: 99%
“…Soil microbial biomass tends to undergo a rapid decline upon topsoil removal and storage, such as is caused by mining Ross et al, 1984b;Visser, Griffiths & Parkinson, 1983;Visser et al, 1984). Build-up of microbial biomass in the residual subsoil normally parallels the build-up of plants and soil organic matter and the microbial biomass has therefore frequently been proposed as an index of soil redevelopment (Ross et al, 1982;Durrall & Parkinson, 1987;Insam & Domsch, 1988;Srivastava, Jha & Singh, 1989;Ross et a / . , 1990).…”
Section: A Wardlementioning
confidence: 99%
“…It has been reported that the quantity of soil microbes was lower in plantations relative to primary or naturally regenerated forests (Yang et al, 1998(Yang et al, , 1999. Interestingly, microbial biomass is the most active element of SOC (Jenkinson & Ladd, 1981;Insam et al, 1988;Ross et al, 1990;Bentham et al, 1992), and alterations in microbial biomass may be an early indication of changes in total organic matter, long before changes in total soil C and N can be reliably detected. Therefore, microbiological characteristics are recommended as useful ecological indicators of stress caused by anthropogenic activities (Powlson et al, 1987;Sparling, 1992;Bosatta & Agren, 1993;Jia et al, 2005;Zheng et al, 2005).…”
mentioning
confidence: 98%
“…An interesting and important fact is that very little is known about the functional diversity and metabolic abilities of microbial communities is spontaneously developing mine spoil (Chodak et al, 2009). Ross et al, (1990) suggested that in the initial stage of the soil restoration, rate of mineralization of soil organic matter is dependent on substrate supply and the size of microbial population. The ratios of microbial biomass C: total C (Insam and Domsch 1988) and respiration: microbial C (Insam and Haselwandter 1989) have been proposed as measures of the success of reclamation efforts (Ross et al, 1990).…”
Section: Role Of Soil Microbial Biomass In Ecological Restoration Of mentioning
confidence: 99%
“…Ross et al, (1990) suggested that in the initial stage of the soil restoration, rate of mineralization of soil organic matter is dependent on substrate supply and the size of microbial population. The ratios of microbial biomass C: total C (Insam and Domsch 1988) and respiration: microbial C (Insam and Haselwandter 1989) have been proposed as measures of the success of reclamation efforts (Ross et al, 1990). Smith and Paul (1990) concluded that monitoring of changes in ratios of fungi to bacteria and in species diversity, biomass estimation could be a powerful method of prediction.…”
Section: Role Of Soil Microbial Biomass In Ecological Restoration Of mentioning
confidence: 99%